Early kinetics of innate and adaptive immune responses during hepatitis B virus infection. Issue 7 (6th February 2009) - Fisicaro, P; Valdatta, C; Boni, C; Massari, M; Mori, C; Zerbini, A; Orlandini, A; Sacchelli, L; Missale, G; Ferrari, C
Abstract : Background and Aim: Innate immunity appears to be silent in acutely heptitis B virus (HBV)-infected chimpanzees, as shown by microarray analysis of intrahepatic gene expression. Whether this observation also applies to HBV pathogenesis in man remains undefined. The aim of this study was thus to characterise natural killer (NK) and CD56 + natural T (NT) cell responses early after human HBV infection and their relationship to the induction of adaptive immunity. Methods: Two HBV-seronegative blood donors who became hepatitis B surface antigen (HBsAg) and HBV DNA positive but had persistently normal alanine aminotransferase (ALT) were followed from a very early stage of HBV infection. The phenotype (CD69 and NKG2D) and function (cytotoxicity and interferon γ (IFNγ) production) of NK and NT cells were analysed. CD4- and CD8-mediated responses were studied in parallel with overlapping peptides covering the entire HBV sequence by ex vivo intracellular cytokine staining (ICS) for IFNγ, interleukin 2 (IL2), IL4 and IL10, and by ex vivo Elispot for IFNγ. Healthy subjects, and patients with chronic and acute HBV infection were studied for comparison. Results: An early induction of both innate and adaptive responses was observed. NK and NT cells showed faster kinetics than HBV-specific T cells with an earlier peak of activity, while CD4 + and CD8 + cell responses were mounted with a similar profile, with higher frequencies of IFNγ-producing CD8 + cells at the peak of the response. Conclusions: The innate immune system is able to sense HBV infection, as shown by the early development of NK and NT cell responses, which probably contribute to contain the HBV infection and to allow timely induction of adaptive responses.